2021
DOI: 10.1177/0963689721994808
|View full text |Cite
|
Sign up to set email alerts
|

Co-Transplantation of Haploidentical Stem Cells and a Dose of Unrelated Cord Blood in Pediatric Patients with Thalassemia Major

Abstract: Allogeneic stem cell transplantation is a cure for patients suffering from thalassemia major (TM). Historically, patients were limited by the selection of donors, while the advancement of haploidentical stem cell transplantation (haplo-SCT) has greatly expanded the donor pool. However, the outcomes of haplo-SCT in TM recipients vary between different programs. In this study, we retrospectively studied 73 pediatric TM patients (median age, 7 years; range, 3 to 14 years) who underwent haplo-cord transplantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Therefore, we used MTX at these adjacent time‐points in addition to PTCy to cover the ‘leaking’ T‐cell reactivity. The combination of PTCy and LD‐MTX was also reported in two other studies 16,49 . However, the rates of aGVHD were high, at 42% and 25% in Grades II–IV 16 and Grades III–IV 49 respectively.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Therefore, we used MTX at these adjacent time‐points in addition to PTCy to cover the ‘leaking’ T‐cell reactivity. The combination of PTCy and LD‐MTX was also reported in two other studies 16,49 . However, the rates of aGVHD were high, at 42% and 25% in Grades II–IV 16 and Grades III–IV 49 respectively.…”
Section: Discussionmentioning
confidence: 52%
“…However, because of the benign nature of thalassaemia, further modifications are required to reduce the incidence of both aGVHD and cGVHD. Another study reported an estimated OS and EFS of 95.26%, with no graft failures observed for 73 thalassaemia paediatric patients who underwent co‐transplantation of haploidentical peripheral grafts and a single dose of unrelated cord blood (given six days after transplant), 16 However, the rates of overall and severe aGVHD were high, at 52% and 25% respectively. In this study, the OS and EFS were excellent at 98.1% and 90.7% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations